THE EFFECT OF RELATIONSHIP MARKETING AND CROSS SELLING ON THE MARKETING PERFORMANCE OF INSURANCE PRODUCTS PT SUN LIFE INDONESIA SALES OFFICE SINGARAJA - Ni Komang Dharmi Yudhi Utami; Trianasari; Putu Indah Rahmawati (Master of Management, Mataram University, 2022)
This study aimed to investigate the effect of relationship marketing and cross selling, either partially or simultaneously, toward the marketing performance of insurance products at PT. Sun Life Indonesia Sales Office Singaraja. The data collection technique was carried out a questionnaire method filled in via Google Form with a Saturated Sampling system with 110 samples of respondents from the financial consultant team. The data analysis technique used multiple linear regression analysis test. The results of the research show that relationship marketing and cross selling have a positive and significant effect on the marketing performance (Y) of insurance products at PT. Sun life Indonesia Sales Office Singaraja, either partially or simultaneously. That is, the stronger the relationship between companies and customers, the marketing performance increases at PT. Sun life Indonesia Sales Office Singaraja. This study aimed to investigate the effect of relationship marketing and cross selling, either partially or simultaneously, toward the marketing performance of insurance products at PT. Sun Life Indonesia Sales Office Singaraja. The data collection technique was carried out a questionnaire method filled in via Google Form with a Saturated Sampling system with 110 samples of respondents from the financial consultant team. The data analysis technique used multiple linear regression analysis test. The results of the research show that relationship marketing and cross selling have a positive and significant effect on the marketing performance (Y) of insurance products at PT. Sun life Indonesia Sales Office Singaraja, either partially or simultaneously. That is, the stronger the relationship between companies and customers, the marketing performance increases at PT. Sun life Indonesia Sales Office Singaraja. Penelitian ini bertujuan untuk menganalisis pengaruh relationship marketing dan cross selling, baik secara partial maupun simultan, terhadap kinerja pemasaran produk asuransi di PT. Sun Life Indonesia Sales Office Singaraja. Teknik pengambilan data menggunakan metode kuisioner yang diisi melalui Google Form dengan sistem Sampling Jenuh dengan 110 sampel responden tim financial consultant. Teknik analisis data menggunakan uji analisis regresi linear berganda. Hasil penelitan menunjukkan bahwa relationship marketing dan cross selling berpengaruh positif dan signifikan terhadap kinerja pemasaran (Y) produk asuransi di PT. Sun life Indonesia Sales Office Singaraja, baik secara parsial maupun simultan. Artinya, semakin kuat hubungan antar perusahaan dengan pelanggan, maka kinerja pemasaran meningkat di PT. Sun life Indonesia Sales Office Singaraja.